Significance of smash and smash-lunge sequence in singles badminton matches in elite players - Lin, Z.; Nosaka, K.; Wilkie, J. C. (International Journal of Performance Analysis in Sport, 2022)
This study examined the number of smashes and smash-lunge sequences in elite men`s singles matches. Semi-final and final match videos of the Olympic Games, Grand-Prix, and World-SuperSeries in 2016 were analysed. Points won from smashes and smash-lunge sequence in a game and an entire match were compared between the winners and losers, and whether points won from the smash-lunge sequence occurred immediately, within three rallies or more were analysed. The game winners scored more (p < 0.05) points than the losers in a game from smashes (4.8 ± 1.9 vs 3.5 ± 1.3 points) and from smash-lunge sequences (4.0 ± 2.8 vs 1.7 ± 1.6 points). Match winners won more (p < 0.05) points from smashes (11.0 ± 2.6) and smash-lunge sequences (7.4 ± 4.8) than match losers (8.2 ± 3.0 and 5.5 ± 3.7, respectively). The match winners won 5-10% more points from the smash-lunge sequence than losers (p < 0.05), and 60% of the points were won immediately from the smash-lunge sequence for both the winners and losers. The smash-lunge sequence is important in badminton. Winners were more effective than the losers at scoring points from this sequence, and in particular, at winning points immediately off the smash-lunge sequence, rather than in the following rallies. Thus, improving the techniques of the smash-lunge sequence is necessary.